Electrochemical-based approaches for the treatment of pharmaceuticals and personal care products in wastewater - Mosur Nagarajan, Aditya; Subramanian, Aishwarya; Prasad Gobinathan, Krishna; Mohanakrishna, Gunda; Sivagami, Krishnasamy (Journal of environmental management, 2023)
In recent times, emerging contaminants (ECs) like pharmaceuticals and personal care products (PPCPs) in water and wastewater have become a major concern in the environment. Electrochemical treatment technologies proved to be more efficient to degrade or remove PPCPs present in the wastewater. Electrochemical treatment technologies have been the subject of intense research for the past few years. Attention has been given to electro-oxidation and electro-coagulation by industries and researchers, indicating their potential to remediate PPCPs and mineralization of organic and inorganic contaminants present in wastewater. However, difficulties arise in the successful operation of scaled-up systems. Hence, researchers have identified the need to integrate electrochemical technology with other treatment technologies, particularly advanced oxidation processes (AOPs). Integration of technologies addresses the limitation of indiviual technologies. The major drawbacks like formation of undesired or toxic intermediates, s, energy expenses, and process efficacy influenced by the type of wastewater etc., can be reduced in the combined processes. The review discusses the integration of electrochemical technology with various AOPs, like photo-Fenton, ozonation, UV/H2O2, O3/UV/H2O2, etc., as an efficient way to generate powerful radicals and augment the degradation of organic and inorganic pollutants. The processes are targeted for PPCPs such as ibuprofen, paracetamol, polyparaben and carbamezapine. The discussion concerns itself with the various advantages/disadvantages, reaction mechanisms, factors involved, and cost estimation of the individual and integrated technologies. The synergistic effect of the integrated technology is discussed in detail and remarks concerning the prospects subject to the investigation are also stated. [Display omitted] •Pharmaceutical and Personal Care products (PPCPs) are persistent organic pollutants.•Concentration and exposure conditions determine the toxicity levels of different PPCPs present in the environment.•Electrochemical combined advanced oxidation methods for the treatment of PPCPs is found to be superior.•PPCPs were found to be completely mineralized by integration with other advanced oxidation processes.